(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Multiple sclerosis is an autoimmune disease, its etiology until know is unknown. Many studies suggested that the environmental risk factors one of them is chlamydia Pneumoniae may play a role in the initiation of the disease. Objectives:To investigate the relationship between previously Chlamydia Pneumoniae infection and multiple sclerosis disease initiation Methods:Sixty patients with multiple sclerosis (30 newly and 30 previously diagnosed), their ages ranged from 13 to 58 years were enrolled in the present study. They attended seeking for treatment or for the diagnoses of multiple sclerosis in outpatient clinic at the Medical City, Baghdad Teaching Hospital, Baghdad in the period from December 2014 till March 2015. In addition, thirty healthy volunteers their gender and ages were matched with patients group were participated as a control. We measured the anti chlamydia Pneumoniae IgG by ELISA technique. Results:The chlamydia Pneumoniae positivity in the multiple sclerosis patients was considerably higher than the control group but the variation was not significant (p > 0.05) and there was no difference between the previously and newly diagnosed multiple sclerosis patients. Conclusion:There is no statistically significant relationship between previously chlamydia Pneumoniae infection and MS disease. Keywords:Multiple sclerosis, chlamydia Pneumoniae